Motivations for posting online reviews in the hotel industry - Gonçalves, Helena Martins (2022)
Some travelers may rely on online reviews (electronic word of mouth [eWOM]) from users who have already experienced a particular hotel before making a hotel reservation. However, only a small percentage of users of eWOM contribute actively with new reviews and evaluations. The understanding of what motivates consumers to write eWOM is very important, in order that hotels can achieve more and better eWOM and, consequently, more reservations. Based on an online survey and using fuzzy-set qualitative comparative analysis, this study identifies different causal combinations of motivations (personal, social benefit, social concern, and consumer empowerment) and demographic characteristics (gender and age) that lead to hotel eWOM. Three configurations exist: being a female older than 35 years old, combined with high social concern and high consumer empowerment; being a female older than 35 years old, combined with high social concern and high personal motivations; and being a male, combined with high social concern, high personal motivations, and high consumer empowerment.